Was evolution worth it? - Kahane, G (Springer Nature, 2022)
The evolutionary process involved the suffering of quadrillions of sentient beings over millions of years. I argue that when we take this into account, then it is likely that when the first humans appeared, the world was already at an enormous axiological deficit, and that even on favorable assumptions about humanity, it is doubtful that we have overturned this deficit or ever will. Even if there’s no such deficit or we can overturn it, it remains the case that everything of value associated with humanity was made possible by our evolutionary history and all that animal suffering. It can seem indecent to regard all that past suffering as having been worth it simply because it was a causal precondition for our existence. But when we consider the realistic alternatives to the way evolution in fact unfolded, there is nevertheless a conditional case for regarding past sentient suffering as a kind of necessary evil.